ZAKAT PRODUKTIF SEBAGAI MEKANISME DISTRIBUSI PENDAPATAN: ANALISIS TRANSFORMASI MUSTAHIK DAN KEBERLANJUTAN EKONOMI DALAM PERSPEKTIF EKONOMI MAKRO ISLAM - Dia Nur Avita Sari; Aulia Devi Rahmawati; Siti Musfiqoh (ISTISMAR, 2026)
This study aims to analyze the role of productive zakat as an income distribution mechanism from the perspective of Islamic macroeconomics. The research employs a descriptive-analytical qualitative method using secondary data obtained from reports published by the National Zakat Agency (BAZNAS). The findings indicate that productive zakat functions as a distribution system through the collection, distribution, and empowerment of mustahik (zakat beneficiaries). the program increases income, supports business development, and promotes economic self-reliance. The sustainability of benefits experienced by mustahik demonstrates that productive zakat contributes to a more equitable distribution of income. therefore, produtive zakat serves as an instrument for achieving economic equity within the framework of islamic economics. Keywords : Productive Zakat, Income Distribution, Economic Suistanability